INCOME DYNAMICS AND CHANGES IN COGNITIVE HEALTH IN OLD AGE. (16th November 2018) - Kim, B; Song, C; Kwon, E
Abstract: Cognitive functioning is critical for independent living in old age. Although cognitive functioning has been demonstrated to decline along with aging, there is limited understanding of differences in cognitive function changes across various income dynamic groups. This study aims to identify patterns of long-term income trajectories and their associations with cognitive function changes in old age. Data came from the seven waves (2002–2014) of Health and Retirement Study, a nationally representative sample of older Americans. Our sample was restricted to respondents over 65 years in 2002, and one person from a household was randomly selected (N=8, 334; Obs.=38, 665). Income was measured by household income-to-needs ratio reflecting the number of family members and inflation rates over time. The cognitive status was measured based on a 27-point cognitive index representing short-term memory, working memory, and speed of processing. A Latent Class Growth Modeling was performed to identify long-term trajectories of income. Hierarchical Linear Modeling was used to analyze the associations between different income trajectory patterns and cognitive function changes over an observation period of 12 years. Four heterogeneous latent classes were considered the best fit for long-term income trajectory patterns: Low (67.8%), Declining (8.7%), Increasing (15.0%), and High-Slow declining (8.5%). Income instability was not found to play a significant role in cognitive functioning, but constantly higher income helps to delay the development of cognitive impairments. This study adds to the limited body of literature on longitudinal health disparities in old age and provides implications for future research and policy on improving cognitive health.